Inventarisasi Sumur Artesis di Desa Cikeusik Kabupaten Pandeglang Provinsi Banten - Anisa Zulfa Salamah; Prastowo (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Cikeusik villagers use groundwater in almost all household activities. Utilization of ground water is done for household or domestic needs. The amount of population is one of the variables of the domestic water needs of an area, the more the population, the higher the amount of water needs. Groundwater inventory activity aims to collect data and explore the existing water resources in Cikeusik Village. Water discharge measurements were carried out on 4 artesian wells and interviews were done to each RT and RW in Cikeusik Village to find out the availability of clean water and the number of wells owned by villagers as a source of clean water. The measured water discharge from each artesian well in Cikeusik Village has an average value of 0.037 Liters / second so that in one day 12700 liters of water can be produced. The calculation results show that the availability of water from artesian wells built by Cikeusik Village only meets the needs of 181 people for one year. The number of Cikeusik villagers who do not yet have private wells is still very much, 944 out of 5820 households. Therefore, further research about groundwater source is recommended in Cikeusik. Research such as prediction of potential groundwater reserves and water quality and ground water level is really essential. Keywords: artesian well, groundwater, inventory, water discharge, water resources